The Impact of Digital Transformation on Enhancing Organizational Innovation (An Applied Study on Commercial Banks Operating in Tripoli, Libya) (Al-Farooq Journal of Sciences, 2026)
Digital transformation has become one of the influential managerial and technological trends shaping the way organizations operate. It is no longer limited to introducing new electronic systems or converting paper-based procedures into digital processes; rather, it has become increasingly associated with redesigning processes, developing organizational capabilities, and transforming work practices and services. This issue is particularly important in the banking sector due to the growing reliance of banks on digital technologies, data, and electronic channels for service delivery and operational management.This study aims to examine the effect of digital transformation on enhancing organizational innovation in commercial banks operating in Tripoli, Libya. To achieve this objective, a research model was developed in which digital transformation is treated as the independent variable comprising four dimensions: digital infrastructure, employees’ digital capabilities, digital leadership, and organizational culture supporting digital transformation. Organizational innovation represents the dependent variable and encompasses administrative innovation, process innovation, service innovation, and innovation in work practices.The study adopts a descriptive-analytical approach and uses a questionnaire as the data collection instrument, based on an assumed sample of 120 employees working in commercial banks in Tripoli. For the purposes of the applied research model, simulated statistical data were used to illustrate how the results can be presented and analyzed. Accordingly, the figures reported in the tables do not represent the findings of an actual field survey. The hypothetical results indicate a positive relationship between digital transformation and organizational innovation, and further suggest that digital leadership and employees’ digital capabilities are among the dimensions most strongly associated with organizational innovation.
Keywords: Digital Transformation, Organizational Innovation, Digital Capabilities, Digital Leadership, Organizational Culture, Commercial Banks, Tripoli, Libya